Efektivitas Metode Index Card Match Dalam Meningkatkan Pemahaman Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam (PAI) Di SMP Tahfidz Qur’an Al-Fatih Bengkalis - Bella Santri; Muhammad Aufa Muis (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The researcher discusses the Index Card Match Method (looking for pairs of cards) which is a fun learning method used to repeat material previously provided. This type of research is field research with a quantitative approach, namely a research method based on the philosophy of positivism. Data collection uses a questionnaire, observation and interviews. After the data was collected, the researcher used the prodact moment formula in order to find out alternative success scores for learning using the index card match method. From the percentage results, the recapitulation of the results of the questionnaire respondents answered the effectiveness of the lecture method in increasing students' learning understanding in Islamic Religious Education (PAI) subjects. has a less good and less high value, because the alternative answers yes are fewer than the alternative no, the percentage result is 44.65. While the research results from the recapitulation of the questionnaire regarding the index card match method in increasing students' learning understanding in the subject of Islamic Religious Education has a value of 89%. This is included in the very good criteria, which means that H0 is rejected, thus the Alternative Hypothesis (Ha) is accepted